A method for deashing of ethylene-cycloolefin copolymers
Patent Information
- Application Number
- CN202611193397.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]为克服现有COC脱灰技术存在的脱除精度不足、工艺损耗大、设备腐蚀严重、批次稳定性差、难以适配高端高纯产品生产等技术缺陷,本发明提出一种高效低损的乙烯-环烯烃共聚物的灰分脱除方法
本发明首创“酸预解离-胺-羰基双位点络合-吸附剂深度截留”三元协同脱灰体系,其中,酸解步骤可打破聚合物对杂质的包裹,为络合剂提供反应位点;由氨基化合物与活泼羰基化合物复配的双位点络合剂可利用氨基弱配位位点捕获低价杂质前驱体、羰基强螯合位点结合高价催化金属,从而实现对全形态金属杂质的广谱络合,其脱灰效率较单一螯合剂提升3~5倍,为吸附提供选择性基础;多孔吸附剂可针对性截留络合产物,实现杂质与聚合物的彻底分离,因此,三者存在强递进协同作用,可将灰分含量稳定控制在10ppm以内(远优于现有技术<100ppm的常规水平);同时,由于采用低酸量温和工艺,其酸用量仅为传统酸洗的1/20,且工艺窗口宽、批次稳定性强,产物收率达98.5%以上,可同时适配光学、医用、半导体领域高端COC的超洁净生产要求,解决了现有技术脱灰精度不足、污染大、损耗高的行业痛点。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer material preparation technology, and specifically relates to a method for deashing ethylene-cycloolefin copolymers. Background Technology
[0002] With the rapid development of my country's optoelectronics, biomedicine, and semiconductor industries, the market demand for high-purity, high-stability, and ultra-clean ethylene-cycloolefin copolymers (COCs) continues to surge. Currently, the industrial preparation of high-performance ethylene-cycloolefin copolymers generally employs metallocene-catalyzed solution copolymerization. This catalytic system boasts high catalytic efficiency and strong controllability in copolymerization, enabling the preparation of structurally uniform and high-performance COC products. However, this process has inherent drawbacks—after the polymerization reaction, a large amount of catalytic metal ions, metal oxides, inorganic salts, and trace amounts of additives remain in the system. These impurities eventually accumulate in the finished polymer product, forming solid ash residue. The residual inorganic ash and metal impurities in the COC product severely damage the optical homogeneity of the material, causing increased haze, decreased transmittance, and scattering defects, significantly reducing optical imaging accuracy and failing to meet the stringent standards of high-end optical devices. During high-temperature melting processing, residual metal impurities catalyze the thermo-oxidative aging of the polymer, leading to material degradation, yellowing, and decreased mechanical strength, significantly deteriorating the product's processing stability and service life. Meanwhile, metal ion impurities in the ash significantly reduce the insulation and dielectric stability of COC materials, severely restricting their application in high-end microelectronics fields such as semiconductors and precision electronics. They also reduce the cleanliness and biocompatibility of the materials, making them unsuitable for medical packaging, sterile consumables, and other applications. Therefore, ash content is a core quality control indicator for defining the grade of ethylene-cycloolefin copolymer products and determining their suitability for high-end applications. The deashing and purification process is a crucial step in the production of high-quality COC, and it has a decisive impact on product performance and industrial applications.
[0003] Currently, mainstream deashing processes in the industry still suffer from many common defects, making it difficult to simultaneously meet the demands of efficient and deep deashing, low product loss, and low-cost industrial production. Traditional acid washing and water washing processes easily generate large amounts of acidic wastewater, corroding equipment and having limited deashing precision, making it difficult to completely remove encapsulated catalyst impurities, leaving trace amounts of ash residue in the finished product. Conventional adsorption deashing methods have low impurity removal efficiency and poor adsorption selectivity, and are insufficient in removing low-valent metal oxides and complexed latent impurities. Problems such as ash return, yellowing, and atomization are prone to occur during long-term storage and high-temperature processing. Multi-stage flash evaporation and repeated solvent precipitation processes are cumbersome, require high equipment investment, and consume huge amounts of solvent, which can easily lead to polymer product loss and increase production costs. In addition, single chelation and adsorption processes have limited adaptability and cannot simultaneously achieve the synergistic removal of multiple types of metal impurities and volatile impurities. Batch deashing stability is poor, and indicators fluctuate greatly, making it difficult to meet the ash control standards of high-end optical, semiconductor, and medical-grade ultrapure COC. Therefore, developing an efficient, low-loss, stable, and pollution-free deashing process to accurately remove residual ash impurities from the COC polymerization system and strictly control the ash content of the product is of great engineering value and market significance for improving the purity, comprehensive performance, and added value of ethylene-cycloolefin copolymer products, realizing the domestic mass production of high-end COC, and filling the domestic technological gap. Summary of the Invention
[0004] To overcome the technical defects of existing COC deashing technologies, such as insufficient removal accuracy, large process losses, severe equipment corrosion, poor batch stability, and difficulty in adapting to the production of high-end and high-purity products, this invention proposes a highly efficient and low-loss method for ash removal from ethylene-cycloolefin copolymers. This invention innovatively employs a ternary synergistic deashing system of "acid pre-dissociation-amine-carbonyl dual-site complexation-adsorbent deep retention," which can significantly reduce the amount of acidic reagents used, effectively alleviate the corrosion and wear of production equipment by acidic media, and reduce the pressure on process wastewater treatment. Simultaneously, a specialized compounded complexing agent is introduced to precisely coordinate and capture ash precursor impurities such as complexed, encapsulated, and low-valent metal oxides in the system, significantly improving the removal capacity of complex impurity systems. A specialized porous adsorbent is used to deeply adsorb and retain complexed metal complexes and trace ultrafine impurity particles, achieving complete impurity separation. Furthermore, a gentle precipitation process using alcohol solvents is combined for product purification, effectively avoiding polymer product loss and consistently controlling the ash content of the finished product below 10 ppm, effectively meeting the production quality control requirements of ultra-high purity COC in high-end optics, precision electronics, and medical materials fields.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A deashing method for ethylene-cycloolefin copolymers addresses the technical challenge of deeply removing encapsulated and complexed metal impurities from COC polymerization systems. First, an acidic reagent activates and dissociates bound metal impurities into free metal ions. Then, a complexing agent composed of an amino compound and an active carbonyl compound coordinates with the metal ions to construct a stable six-membered chelate ring structure, transforming the difficult-to-remove metal impurities into large-molecule polar complexes. Subsequently, a porous adsorbent is used to selectively adsorb and retain the chelate complexes, achieving efficient separation of impurities from the polymer mother liquor. Finally, a poor solvent, an alcohol, is used to precipitate the polymer, yielding a high-purity COC product with low ash content.
[0006] Specifically, the method includes the following steps: 1) Acid hydrolysis activation: Under high temperature conditions, acidic reagents are used to acid hydrolyze the polymerization mother liquor of ethylene-cycloolefin copolymer to destroy the metal impurity encapsulation structure and fully dissociate the bound and complexed metal impurities in the system into free metal ions; 2) Chelation coordination: Add a complexing agent to the acid-activated polymer solution to perform chelation, so as to utilize its multifunctional group synergistic coordination effect to combine with free metal ions and form a structurally stable six-membered chelate ring, thereby realizing the fixation and transformation of metal impurities. 3) Adsorption purification: The fully chelated polymer solution is passed into an adsorption column filled with porous adsorbent. The high specific surface area and selective adsorption characteristics of the porous material are used to deeply adsorb and retain the polar metal chelates, so as to remove trace metal complexes and ultrafine inorganic impurities in the system and obtain purified polymer mother liquor. 4) Precipitation: A poor solvent is added to the purified polymer solution after adsorption treatment to disrupt the homogeneous system of the polymer solution, allowing the polymer to fully precipitate. After separation and drying, a high-purity ethylene-cycloolefin copolymer with low ash content is obtained.
[0007] Further, the acidic reagent in step 1) is selected from at least one of inorganic acids or organic acids, or an aqueous solution thereof. The inorganic acids include one or more of hydrochloric acid, nitric acid, and hypochlorous acid; the organic acids include one or more of formic acid, acetic acid, butyric acid, isobutyric acid, benzoic acid, oxalic acid, citric acid, tartaric acid, and benzenesulfonic acid.
[0008] Further, the acid hydrolysis in step 1) is carried out at a temperature of 90~150 ℃ for 1~3 h.
[0009] Further, the amino compound in step 2) is selected from one or more of the following: amino acids such as glycine, alanine, lysine, phenylalanine, glutamic acid, and cysteine; amine compounds such as o-phenylenediamine, aniline, octylamine, triethylamine, triethanolamine, n-hexylamine, ethanolamine, and propylenediamine; and acylhydrazine compounds such as acetylhydrazine, benzoylhydrazine, isonicohydrazine, succinylhydrazine, oxalohydrazine, and p-nitrobenzoylhydrazine.
[0010] Further, the active carbonyl compound in step 2) is selected from one or more of ketones, aldehydes, and ester complexing agents of C3 to C40, preferably acetone, propylene glycol, acetylacetone, benzoylacetone, cyclopentanedione, trifluoroacetylacetone, ethyl acetoacetate, and benzaldehyde.
[0011] Further, in step 2), the molar ratio of the amino compound to the active carbonyl compound in the complexing agent is 1:1.
[0012] Furthermore, in step 2), the amount of complexing agent added is calculated as 0.1 mol per 100 mL of polymer solution.
[0013] Further, the chelation temperature in step 2) is 90~150 ℃, and the time is 1~5 h.
[0014] Further, in step 3), the porous adsorbent is selected from one or more of porous metal oxides, porous inorganic non-metallic oxides, and molecular sieves. Specifically, the porous metal oxide is selected from one or more of alumina, zinc oxide, copper oxide, chromium oxide, magnesium oxide, and calcium oxide; the porous inorganic non-metallic oxide is selected from one or more of silica gel and porous silica; and the molecular sieve is selected from one or more of X-type, Y-type, and ZSM-type molecular sieves.
[0015] Furthermore, in step 3), the adsorption treatment temperature is 100~180℃, and the residence time of the material in the column is 1~30min.
[0016] Further, the undesirable solvent in step 4) is a C1~C10 alcohol, preferably one or more of methanol, ethanol, isopropanol, butanol, and pentanol.
[0017] The significant advantages of this invention are: This invention pioneers a ternary synergistic deashing system of "acid pre-dissociation-amine-carbonyl dual-site complexation-adsorbent deep retention". The acid dissociation step breaks the polymer's encapsulation of impurities, providing reaction sites for the complexing agent. The dual-site complexing agent, composed of an amino compound and an active carbonyl compound, utilizes the weak coordination sites of the amino group to capture low-valent impurity precursors and the strong chelating sites of the carbonyl group to bind high-valent catalytic metals, thus achieving broad-spectrum complexation of all metal impurities. Its deashing efficiency is 3-5 times higher than that of a single chelating agent, providing a selective basis for adsorption. The porous adsorbent can specifically retain the complexed impurities. The product achieves complete separation of impurities and polymers. Therefore, the three have a strong progressive synergistic effect, which can stably control the ash content within 10ppm (far superior to the conventional level of <100ppm in existing technologies). At the same time, due to the use of low acid and mild process, the acid consumption is only 1 / 20 of that of traditional acid washing, and the process window is wide, the batch stability is strong, and the product yield is over 98.5%. It can simultaneously meet the ultra-clean production requirements of high-end COC in the optical, medical, and semiconductor fields, and solve the industry pain points of insufficient ash removal precision, high pollution, and high loss in existing technologies. Detailed Implementation
[0018] A method for deashing ethylene-cycloolefin copolymers, comprising the following steps: 1) Add an acidic reagent to the polymerization mother liquor of the ethylene-cycloolefin copolymer and activate it by acid hydrolysis at 90~150 °C for 1~3 h to dissociate metal impurities into free metal ions; 2) Add a complexing agent consisting of an amino compound and an active carbonyl compound in a molar ratio of 1:1 to the acid-activated polymer solution at a rate of 0.1 mol / 100 mL, and chelate at 90~150 °C for 1~5 h to achieve the fixation and transformation of metal impurities. 3) Pass the fully chelated polymer solution into an adsorption column filled with porous adsorbent and selectively adsorb and retain it at 100~180℃ (the residence time of the material in the column is 1~30 min) to remove trace metal complexes and ultrafine inorganic impurities in the system and obtain refined polymer mother liquor. 4) Add C1~C10 alcohols as poor solvents to the purified polymer solution after adsorption treatment to allow the polymer to be fully precipitated. After separation and drying, a high-purity ethylene-cycloolefin copolymer with low ash content is obtained.
[0019] In step 1), the acidic reagent is selected from at least one of inorganic acids or organic acids, or an aqueous solution thereof. The inorganic acids include one or more of hydrochloric acid, nitric acid, and hypochlorous acid; the organic acids include one or more of formic acid, acetic acid, butyric acid, isobutyric acid, benzoic acid, oxalic acid, citric acid, tartaric acid, and benzenesulfonic acid.
[0020] The amino compound mentioned in step 2) is selected from amino acids such as glycine, alanine, lysine, phenylalanine, glutamic acid, and cysteine; amine compounds such as o-phenylenediamine, aniline, octylamine, triethylamine, triethanolamine, n-hexylamine, ethanolamine, and propylenediamine; and acylhydrazine compounds such as acetylhydrazine, benzoylhydrazine, isonicohydrazine, succinylhydrazine, oxalohydrazine, and p-nitrobenzoylhydrazine. The active carbonyl compound is selected from one or more C3-C40 ketones, aldehydes, and ester complexing agents, preferably acetone, propylene glycol, acetylacetone, benzoylacetone, cyclopentanedione, trifluoroacetylacetone, ethyl acetoacetate, and benzaldehyde.
[0021] The porous adsorbent mentioned in step 3) is selected from one or more of porous metal oxides, porous inorganic non-metal oxides, and molecular sieves. Specifically, the porous metal oxide is selected from one or more of alumina, zinc oxide, copper oxide, chromium oxide, magnesium oxide, and calcium oxide; the porous inorganic non-metal oxide is selected from one or more of silica gel and porous silica; and the molecular sieve is selected from one or more of X-type, Y-type, and ZSM-type molecular sieves.
[0022] To make the content of this invention easier to understand, the technical solution of this invention will be further described below with reference to specific embodiments, but this invention is not limited thereto.
[0023] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0024] The ethylene-cycloolefin copolymer (COC) slurry used in the examples was obtained by reaction in a high-temperature, high-pressure stainless steel batch reactor. The specific reaction process was as follows: before the reaction, the reactor system was purged with nitrogen three times at 130°C, and then ethylene gas was repeatedly introduced to purge three times to completely remove oxygen. After that, the system temperature was set to 110°C. After the temperature stabilized, the reactor was sealed, the feed pipeline valve was opened, and 0.2 L of norbornene monomer (74% by mass), 1.2 L of toluene solvent, and 1.0 L of methylaluminoxane (MAO) co-catalyst were added to the system in sequence under a nitrogen protective atmosphere. After stirring and premixing for 5 min, 600 μmol of diphenylmethylene (cyclopentadiene) (9-fluorenyl)zirconium dichloride, the mixture was aged for another 10 min, and then ethylene monomer was introduced to initiate polymerization (pressure set to 0.5 MPa). The reaction was terminated after 20 min, and finally about 2 L of COC slurry with a solid content of 10 wt% was obtained. Example 1
[0025] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of a composite complexing agent prepared by aniline and acetylacetone in a molar ratio of 1:1, and continue stirring at 120℃ for 2 h to obtain COC complexed polymer solution.
[0026] (2) Weigh 100 g of activated alumina adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature of 150°C and maintain the temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for adsorption for 5 min. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. Characterization by inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the residual aluminum content in the sample was 5 ppm and the zirconium content was 0 ppm. Example 2
[0027] (1) Take 100 mL of COC slurry, add 0.5 mL of 1 mol / L citric acid solution, and stir at 120℃ for 1 h; then add 40 mL of composite complexing agent prepared by aniline and acetylacetone in a molar ratio of 1:1, and continue to stir at 120℃ for 2 h to obtain COC complexed polymer solution.
[0028] (2) Weigh 100 g of activated alumina adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150°C and maintain a stable temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for 5 min for adsorption. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization showed that the residual aluminum content in the sample was 6 ppm and the zirconium content was 0 ppm. Example 3
[0029] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of composite complexing agent prepared by aniline and benzaldehyde in a molar ratio of 1:1, and continue to stir at 120℃ for 2 h to obtain COC complexed polymer solution.
[0030] (2) Weigh 100 g of activated alumina adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150°C and maintain a stable temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for 5 min for adsorption. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization showed that the residual aluminum content in the sample was 5 ppm and the zirconium content was 0 ppm. Example 4
[0031] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of a composite complexing agent prepared by triethylamine and acetylacetone in a molar ratio of 1:1, and continue stirring at 120℃ for 2 h to obtain COC complexed polymer solution.
[0032] (2) Weigh 100 g of activated alumina adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150°C and maintain a stable temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for 5 min for adsorption. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization showed that the residual aluminum content in the sample was 4 ppm and the zirconium content was 0 ppm. Example 5
[0033] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of a composite complexing agent prepared by ethanolamine and acetylacetone in a molar ratio of 1:1, and continue to stir at 120℃ for 2 h to obtain COC complexed polymer solution.
[0034] (2) Weigh 100 g of activated alumina adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150°C and maintain a stable temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for 5 min for adsorption. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization showed that the residual aluminum content in the sample was 9 ppm and the zirconium content was 0 ppm. Example 6
[0035] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of a composite complexing agent prepared by aniline and acetylacetone in a molar ratio of 1:1, and continue stirring at 120℃ for 2 h to obtain COC complexed polymer solution.
[0036] (2) Weigh 100 g of microporous silica gel adsorbent (100~200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150℃ and maintain a stable temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for adsorption for 5 min. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization showed that the residual aluminum content in the sample was 8 ppm and the zirconium content was 0 ppm. Example 7
[0037] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of a composite complexing agent prepared by aniline and acetylacetone in a molar ratio of 1:1, and continue stirring at 120℃ for 2 h to obtain COC complexed polymer solution.
[0038] (2) Weigh 100 g of 13X type molecular sieve adsorbent (100~200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150℃ and maintain the temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for adsorption for 5 min. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization test showed that the residual aluminum content in the sample was 9 ppm and the zirconium content was 0 ppm. Example 8
[0039] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of a composite complexing agent prepared by aniline and acetylacetone in a molar ratio of 1:1, and continue stirring at 120℃ for 2 h to obtain COC complexed polymer solution.
[0040] (2) Weigh 100 g of porous calcium oxide adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150°C and maintain a stable temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for 5 min for adsorption. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization showed that the residual aluminum content in the sample was 8 ppm and the zirconium content was 0 ppm. Example 9
[0041] (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of a composite complexing agent prepared by aniline and acetylacetone in a molar ratio of 1:1, and continue stirring at 120℃ for 2 h to obtain COC complexed polymer solution.
[0042] (2) Weigh 100 g of porous titanium dioxide adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150 °C and maintain the temperature. Then, pass the above COC complex polymer solution into the adsorption column and retain it for adsorption for 5 min. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample. ICP-OES characterization showed that the residual aluminum content in the sample was 10 ppm and the zirconium content was 0 ppm.
[0043] Comparative Example 1 Take 100 mL of COC slurry and inject it directly into excess anhydrous ethanol for precipitation. The resulting white solid product is the un-ashed COC sample.
[0044] Characterization tests using ICP-OES showed that the residual aluminum content in the sample was 10988 ppm and the zirconium content was 30 ppm.
[0045] Comparative Example 2 (1) Take 100 mL of COC slurry, add 40 mL of a composite complexing agent prepared by triethylamine and acetylacetone in a molar ratio of 1:1, and stir at 120℃ for 2 h to obtain COC complexed polymer solution.
[0046] (2) Same as step (2) in Example 4.
[0047] The residual aluminum content in the sample was determined to be 154 ppm and the zirconium content to be 5 ppm by ICP-OES characterization.
[0048] Comparative Example 3 (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h to obtain COC polymerization liquid.
[0049] (2) Same as step (2) in Example 4.
[0050] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 497 ppm and the zirconium content was 10 ppm.
[0051] Comparative Example 4 (1) Same as step (1) in Example 4.
[0052] (2) The obtained COC complex polymer solution was directly injected into excess anhydrous ethanol for precipitation. The resulting white solid product was the purified COC sample.
[0053] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 243 ppm and the zirconium content was 8 ppm.
[0054] Comparative Example 5 (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h to obtain COC polymerization liquid.
[0055] (2) The obtained COC polymer solution was directly injected into excess anhydrous ethanol for precipitation. The resulting white solid product was the purified COC sample.
[0056] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 188 ppm and the zirconium content was 4 ppm.
[0057] Comparative Example 6 (1) Take 100 mL of COC slurry, add 40 mL of a composite complexing agent prepared by triethylamine and acetylacetone in a molar ratio of 1:1, and stir at 120℃ for 2 h to obtain COC complexed polymer solution.
[0058] (2) The obtained COC complex polymer solution was directly injected into excess anhydrous ethanol for precipitation. The resulting white solid product was the purified COC sample.
[0059] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 243 ppm and the zirconium content was 6 ppm.
[0060] Comparative Example 7 Weigh 100 g of activated alumina adsorbent (100-200 mesh) and pack it into an adsorption column. Proceed to a temperature program of 150°C and maintain this temperature. Then, pass 100 mL of COC slurry into the adsorption column and allow it to adsorb for 5 min. After adsorption is complete, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample.
[0061] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 583 ppm and the zirconium content was 7 ppm.
[0062] Comparative Example 8 (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of triethylamine and continue stirring at 120℃ for 2 h to obtain COC complex polymer solution.
[0063] (2) Same as step (2) in Example 4.
[0064] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 568 ppm and the zirconium content was 4 ppm.
[0065] Comparative Example 9 (1) Take 100 mL of COC slurry, add 0.5 mL of concentrated hydrochloric acid, and stir at 120℃ for 1 h; then add 40 mL of acetylacetone and continue stirring at 120℃ for 2 h to obtain COC complex polymer solution.
[0066] (2) Same as step (2) in Example 4.
[0067] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 316 ppm and the zirconium content was 4 ppm.
[0068] Comparative Example 10 (1) Same as step (1) in Example 4.
[0069] (2) Weigh 100 g of activated carbon (100~200 mesh) and pack it into the adsorption column. Proceed to the temperature program of 150℃ and keep the temperature stable. Then, pass the above COC complex polymer solution into the adsorption column and retain it in the column for adsorption for 5 min. After the adsorption is completed, drain the polymer solution from the column and inject it into excess anhydrous ethanol for precipitation. The resulting white solid product is the purified COC sample.
[0070] Characterization tests using ICP-OES showed that the residual aluminum content in the obtained sample was 362 ppm and the zirconium content was 3 ppm.
[0071] As can be seen from the above, the integrated purification process of "acid activation and freeing - complex coordination chelation - column porous adsorption - alcohol phase precipitation" provided by the present invention can achieve efficient dissociation, precise complexation, deep retention and complete removal of ash precursor metal impurities step by step, and stably control the ash content of the COC product below 10 ppm, so as to effectively meet the production quality control requirements of ultra-high purity COC in the fields of high-end optics, precision electronics and medical materials.
[0072] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.
Claims
1. A method for deashing ethylene-cycloolefin copolymers, characterized in that, Includes the following steps: 1) Acid hydrolysis activation: The polymerization mother liquor of ethylene-cycloolefin copolymer is acid hydrolyzed with acidic reagent to activate and dissociate the bound and complexed metal impurities in the system into free metal ions; 2) Chelation coordination: A complex complexing agent composed of amino compounds and active carbonyl compounds is added to the acid-activated polymer solution to chelate the free metal ions and form a stable six-membered chelate ring structure. 3) Adsorption purification: The fully chelated polymer solution is selectively adsorbed and retained using a porous adsorbent to achieve efficient separation of impurities from the polymer; 4) Precipitation: Add a poor solvent to the purified polymer solution after adsorption treatment to allow the polymer to fully precipitate. After separation and drying, a high-purity ethylene-cycloolefin copolymer with low ash content is obtained.
2. The deashing method for ethylene-cycloolefin copolymers according to claim 1, characterized in that, Step 1) The acidic reagent is selected from at least one of inorganic acids or organic acids or their aqueous solutions.
3. The deashing method for the ethylene-cycloolefin copolymer according to claim 1, characterized in that, Step 1) The acid hydrolysis temperature is 90~150 ℃ and the time is 1~3 h.
4. The deashing method for ethylene-cycloolefin copolymers according to claim 1, characterized in that, Step 2) The molar ratio of amino compound to active carbonyl compound in the complexing agent is 1:
1.
5. The deashing method for ethylene-cycloolefin copolymers according to claim 4, characterized in that, The amino compound is selected from one or more of amino acids, amines, or hydrazides; the active carbonyl compound is selected from one or more of C3-C40 ketones, aldehydes, or ester complexing agents.
6. The deashing method for ethylene-cycloolefin copolymers according to claim 1, characterized in that, In step 2), the amount of complexing agent added is calculated as 0.1 mol per 100 mL of polymer solution.
7. The deashing method for the ethylene-cycloolefin copolymer according to claim 1, characterized in that, Step 2) The chelation temperature is 90~150 ℃ and the time is 1~5 h.
8. The deashing method for ethylene-cycloolefin copolymers according to claim 1, characterized in that, Step 3) The porous adsorbent is selected from one or more of porous metal oxides, porous inorganic non-metal oxides, and molecular sieves.
9. The deashing method for the ethylene-cycloolefin copolymer according to claim 1, characterized in that, Step 3) The selective adsorption and retention process is carried out at a temperature of 100~180℃ for 1~30 min.
10. The deashing method for ethylene-cycloolefin copolymers according to claim 1, characterized in that, Step 4) The undesirable solvent is an alcohol of C1 to C10.